ANALISIS STILISTIKA LIRIK LAGU-LAGU PADI - Adha, Teti Laila (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The song lyric is literary works that contains the outpouring of personal feelings, emotions, and expressions of soul-shaped experiences in the form of the composition of words in a song. The aims of this research is to discover and descripe the stylistic aspects of the lyrics of Padi songs. Problems in this research include analysis of stylistic aspects of figurative language and imagery and the implementation design of this research in Indonesian language learning. The research method in this research is descriptive qualitative method and using stylistic approach. The data source in this research is the lyrics of Padi songs. Based on the result of this research, the conclusion are 1) the stylistic aspects of figurative language contained in the lyrics of Padi songs, namely the figurative language comparison, metaphor, epic, personification, metonimia, sinekdoki, allegori and epitet. 2) the stylistic aspects of imagery contained in the lyrics of Padi songs, namely visual imagery, auditory imagery, thermal imagery, taste imagery, smell imagery and movement imagery. This research is expected to be a reference for other researchers who researching stylistic aspects in the lyrics of Padi songs as well as references of literary teaching materials for teachers in learning at school. Keywords: song lyric, padi, stylistic